Does Applying Biomedical Knowledge Improve Diagnostic Performance When Solving Electrolyte Problems? - Mclaughlin, Kevin; Novak, Kerri; Rikers, Remy; Schmidt, Henk (Canadian Medical Education Journal, 2010)
Introduction. If physicians apply clinical rather than biomedical knowledge when diagnosing, why do we use the basic sciences as the foundation for clinical teaching? In this study we evaluated the contribution of biomedical knowledge to diagnostic performance when solving electrolyte problems. Method. We asked 13 medical students and 19 nephrologists to solve electrolyte problems while thinking aloud, and determined biomedical knowledge application by protocol analysis. We used logistic regression to study the association between biomedical concepts, clinical experience, and performance. Results. Students and nephrologists applied a similar number of biomedical concepts per case (1.8 (±1.1) vs. 1.8 (±1.2), respectively, p = 0.8), but nephrologists were more successful (86.8% vs. 63.5%, p = 0.003). We found a significant interaction between expertise and applying biomedical concepts (p < 0.05). For students the odds of success increased significantly with applying biomedical concepts (odds ratio 4.66 [2.07, 10.48], p < 0.001), whereas for nephrologists there was only a trend towards improved performance (odds ratio 1.72 [0.94, 3.11], p = 0.07). Conclusions. Our results suggest that improving biomedical knowledge of students should improve their performance on electrolyte problems. The performance of experienced physicians may also be improved, but this requires further study before teaching recommendations can be made.